699 Incidence of COPD in primary and secondary outcomes in patients undergoing a TAVI. (8th December 2021) - Alkhoury, Elie; Prandi, Francesca Romana; Pensabene, Giulia; Di Luozzo, Marco; Marchei, Massimo; Macrini, Massimiliano; Romeo, Francesco; Muscoli, Saverio
Abstract: Aims: The association between severe chronic obstructive pulmonary disease (COPD) and in-hospital mortality (IHM) as well as incidence of post-procedural intubation and length of in-hospital stay (LOHS) in patients with severe aortic stenosis (AS) undergoing transfemoral (TF) transcatheter aortic valve implantation (TAVI) is still unclear. We evaluated the impact of severe COPD on IHM, post-procedural tracheal intubation and LOHS in patients with severe AS undergoing TF TAVI. Methods: We retrospectively analysed a total of 550 consecutive patients who underwent transfemoral TAVI in our centre between 2011 and 2021. We divided the patients in Group 1 (affected by severe COPD) and Group 2 (without COPD). We further divided the patients affected by COPD into Subgroup A (on COPD medical treatment) and Subgroup B (without COPD medical treatment). Results: A total of 550 patients who underwent TF TAVI were included in this analysis. 38.55% ( n =212) had a diagnosis of COPD (Group 1) and 61.45% ( n =338) were not affected by COPD (Group 2). In Group 1, 29.38% ( n =62) of patients were receiving medical treatment for COPD (Subgroup A), while 70.6% ( n =149) were not on COPD medications (Subgroup B). The mean age was 81.83±6.67 in Group 1 vs. 81.33±7.21 in Group 2 ( P =0.45), and 82.12±7.6 in Subgroup A vs. 82.14±6.82 in Subgroup B ( P =0.98). The gender distribution showed 127 (45%) men in Group 1 vs. 96 (50%) men in Group 2 ( P =0. 33), and 21 (42%) men in Subgroup 1 vs. 75 (53%) men in Subgroup B ( P =0.28). The mean EUROSCOREII was 8.26±7.03 in Group 1 vs. 6.81± 7.57 in Group 2, P = 0.11, and 7.24±5.49 in Subgroup A vs. 9.30±7.5 in Subgroup B, P =0.52. There was no difference observed for in-hospital mortality between Group 1 and Group 2 (0.04% vs. 0.05%; P =0.6) and between Subgroup A and Subgroup B (0.04% vs. 0.04%; P =0.7). Similarly, the incidence of post-procedural intubation was comparable between Group 1 and Group 2 (0.06% vs. 0.03%; P =0.18), and between Subgroup A and Subgroup B (0.08% vs. 0.05%; P =0.78). Finally, also the mean length of in-hospital stay was similar between Group 1 and Group 2 (10±4.46 days vs. 9.68± 5.02 days; P =0.47), and between Subgroup A and Subgroup B (10.36±4.24 days vs. 9.87±4.54 days; P =0.5). Conclusions: In patients with severe aortic stenosis treated with transfemoral TAVI, the presence of severe COPD does not affect in-hospital mortality, incidence of post-procedural intubation and length of in-hospital stay. COPD medications do not impact any of the outcomes evaluated. Therefore, TF TAVI is a safe procedure also for patients affected by severe chronic obstructive pulmonary disease that are not on COPD medications.